Particulate Organic Carbon Deconstructed: Molecular and Chemical Composition of Particulate Organic Carbon in the Ocean - Jenan J. Kharbush; Hilary G. Close; Benjamin A. S. Van Mooy; Carol Arnosti; Rienk H. Smittenberg; Frédéric A. C. Le Moigne; Gesine Mollenhauer; Gesine Mollenhauer; Barbara Scholz-Böttcher; Igor Obreht; Boris P. Koch; Kevin W. Becker; et al. (Frontiers in Marine Science, 2020)
The dynamics of the particulate organic carbon (POC) pool in the ocean are central to the marine carbon cycle. POC is the link between surface primary production, the deep ocean, and sediments. The rate at which POC is degraded in the dark ocean can impact atmospheric CO2 concentration. Therefore, a central focus of marine organic geochemistry studies is to improve our understanding of POC distribution, composition, and cycling. The last few decades have seen improvements in analytical techniques that have greatly expanded what we can measure, both in terms of organic compound structural diversity and isotopic composition, and complementary molecular omics studies. Here we provide a brief overview of the autochthonous, allochthonous, and anthropogenic components comprising POC in the ocean. In addition, we highlight key needs for future research that will enable us to more effectively connect diverse data sources and link the identity and structural diversity of POC to its sources and transformation processes.